Combining Ozonated Autohemotherapy with Pharmacological Therapy for Comorbid Insomnia and Myofascial Pain Syndrome: A Prospective Randomized Controlled Study - Wang Shen; Ning Liu; Zhonghua Ji; Hongwei Fang; Feng Liu; Wei Zhang; Xiuqin Yu; Mingxia Wang; Jinyuan Zhang; Xiangrui Wang (Pain Research and Management)
Objective. To examine the efficacy and safety of ozonated autohemotherapy (O3-AHT) combined with pharmacological therapy for comorbid insomnia and myofascial pain syndrome (MPS). Materials and Methods. One hundred and eighteen patients were randomly divided into two groups: the control group (N = 50) and the O3-AHT group (N = 53). Patients in both groups were given the same pharmacological management for three weeks. Patients in the O3-AHT group were treated with ozonated autohemotherapy (the concentration of ozone was 20 µg/ml in the first week, 30 µg/ml in the second week, and 40 µg/ml in the third week) combined with pharmacological therapy. Primary (the insomnia severity index (ISI) and visual analogue scale (VAS)) and secondary outcomes (the Epworth sleepiness scale (ESS), polysomnography data, the anxiety and preoccupation about sleep questionnaire (APSQ), the beck depression index (BDI), and the multidimensional fatigue inventory (MFI)) were examined at pretreatment, posttreatment, 1 month, and 6 months. Results. Fifty patients in the control group and fifty-three patients in the O3-AHT group completed the study. In both groups, insomnia and pain symptoms were relieved significantly compared with pretreatment. Compared with the control group, the O3-AHT group had significantly improved sleep quality, pain, and negative mood at different time points. No adverse complications were observed in either group. Conclusion. Compared with pharmacological therapy alone, ozonated autohemotherapy combined with pharmacological therapy can ameliorate insomnia, reduce pain intensity, improve negative mood, and alleviate fatigue more effectively without serious adverse complications.